From Grant to Growth: Long-term Economic Sustainability of Productive Zakat for Asnaf (Contrarius Series: Law & Social Justice, 2026)
This study examines the transformation of zakat assistance from one off relief to sustained, productive support for asnaf through a long-term economic sustainability. The study aims to analyze how productive zakat strengthens beneficiaries as participants in an inclusive socioeconomy, to map the Shariah legal framework that enables productive modalities, and to assess the practical implementation of productive zakat by Malaysian zakat institutions and partner agencies over time. Using multi wave data from program records, beneficiary surveys, and follow up interviews, the findings reveal that access to Shariah compliant startup capital paired with mentoring, financial literacy, and values based entrepreneurship training is essential for expanding market participation, raising business survival rates, and improving household resilience. Outcomes are further enhanced when beneficiaries adopt simple digital tools such as mobile bookkeeping, cashless payments, online marketplaces, social media promotion, and data driven monitoring to increase reach and operational efficiency. Existing frameworks, including state zakat enactments, risk sharing, and transparency in Islamic jurisprudence, support this transition by enabling compliant financing, structured capacity building, and accountable oversight. Nevertheless, policy refinements are needed to strengthen beneficiary protection, data privacy, standardized impact measurement, and clearer guidance on disbursement modalities and performance thresholds. The study also highlights regional and international platforms, including OIC and G20 forums, as strategic opportunities for aligning standards, crowding in partnerships, and scaling best practices. By leveraging productive capital, digital enablement, and cross sector collaboration, zakat institutions can accelerate the journey from grant to growth and contribute to sustainable and inclusive economic development for asnaf.